2022
DOI: 10.26505/djm.22026390223
|View full text |Cite
|
Sign up to set email alerts
|

The association between obesity and irritable bowel syndrome among a sample of patients attending the primary health care centers in Erbil city

Abstract: Background: Irritable bowel syndrome and obesity are two prevalent conditions in our community which may be associated with each other according to some literature. Both have significant impact on the community.Objective: To find the prevalence of irritable bowel syndrome, its association with general and central obesity, as well as to find its sociodemographic characteristics, and effect of some personal health habits on it.Patients and Methods: In this cross-sectional study, a sample of 248 subjects, 105 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…The research reveals no association between obesity and IBS. It is consistent with previous research that found no significant difference between BMI and IBS [20], [21]. IBS is a functional GI disorder characterized by recurrent abdominal pain and stool frequency and abnormalities.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The research reveals no association between obesity and IBS. It is consistent with previous research that found no significant difference between BMI and IBS [20], [21]. IBS is a functional GI disorder characterized by recurrent abdominal pain and stool frequency and abnormalities.…”
Section: Resultssupporting
confidence: 93%
“…2, June 2024: 804-809 806 which was higher than in other Asian countries like Saudi Arabia, where the prevalence was 17.6%, and more significant than the global prevalence of IBS of 4.1% [19]. In our study, females were twice as likely as males to develop IBS, or a ratio of 2:1, consistent with previous studies [20], [21]. The role of sex hormones in the etiology of IBS can be deduced from epidemiological data on the prevalence of the disease in men and women.…”
Section: Resultssupporting
confidence: 89%